End User Computing Satisfaction of Hospital Information System in Mitra Delima Hospital - Ida Herwati; Jennyla Puspitaning Ayu; Luthfiyah Mustafida (Jurnal Manajemen Kesehatan Indonesia, 2023)
Mitra Delima Hospital as one of the health facilities in providing its services is required to carry out the management and development of SIMRS in accordance with Minister of Health Regulation Number 82 of 2013 with the aim of supporting and improving the health service process at the hospital. The aim of this research is to analyze user satisfaction of the Hospital Management Information System (SIMRS) using the End User Computing Satisfaction (EUCS) method at Mitra Delima Hospital. This type of quantitative research, the research sample used was 35 health workers at Mitra Delima Hospital. The instrument uses a questionnaire and the analysis technique uses linier regression analysis. The research results showed that some respondents were very satisfied with the use of the Hospital Management Information System (SIMRS) using the End User Computing Satisfaction (EUCS) method at Mitra Delima Hospital. The regression analysis showed that content (p value 0,001) and timeliness (p value 0,03) influence the user satisfaction,  while the other three which is accuracy, appearance and ease of use have no influence on user satisfaction. In the simultaneously analysis showed that there is an influence between all independents variables to users satisfaction (p value 0,00; Rsquare  0,935)at Mitra Delima Hospital. It can be concluded that overall respondents are satisfied with the use of the Hospital Management Information System (SIMRS) using the End User Computing Satisfaction (EUCS) method at Mitra Delima Hospital. Mitra Delima Hospital can maintain and increase the level of satisfaction with using SIMRS using the EUCS method, where it can provide additional training to officers in using SIMRS.